2021
DOI: 10.3389/fneur.2021.746035
|View full text |Cite
|
Sign up to set email alerts
|

Effective Treatment of Postherpetic Neuralgia at the First Branch of the Trigeminal Nerve by High-Voltage Pulsed Radiofrequency

Abstract: Background: Postherpetic neuralgia (PHN) is one of the most common and serious complications of herpes zoster. PHN of the first branch of the trigeminal nerve is painful and difficult to treat, as no definitive effective treatment is available. The aim of this retrospective study was to observe the efficacy and safety of treatment of PHN of the first branch of the trigeminal nerve with high-voltage pulsed radiofrequency (PRF) of the supraorbital nerve.Methods: Fifty-two patients diagnosed with the PHN of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…This allows PRF to ease PHN without changing the nerve fiber structure (23,24). In this study, pain was relieved after PRF therapy, which is consistent with the findings of previous studies (10)(11)(12)(13). However, other studies reported that PRF therapy efficacy in treating PHN was not ideal (14,15).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This allows PRF to ease PHN without changing the nerve fiber structure (23,24). In this study, pain was relieved after PRF therapy, which is consistent with the findings of previous studies (10)(11)(12)(13). However, other studies reported that PRF therapy efficacy in treating PHN was not ideal (14,15).…”
Section: Discussionsupporting
confidence: 91%
“…However, there are different opinions about the effectiveness of PRF therapy for PHN. Some reports believe that PRF can effectively relieve pain and improve the quality of life of patients with PHN (10)(11)(12)(13). Other reports suggest that PRF is not the ideal therapy for treating neuropathic pain (14) and that PRF does not significantly relieve nerve root pain (15).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we used PRF technique to precisely intervene in the function of DRG. PRF had been proven to be an effective technique for pain management [ 10 – 12 , 20 22 ]. PRF technique generates a high-voltage but low-temperature (<40°C) environment around target nerve through high-frequency pulsed current, which can affect the conduction of pain sensory [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 28 studies remained for full-text screening. Finally, 6 studies [20][21][22][27][28][29] with 423 patients were included for data extraction and final analysis (Figure 1).…”
Section: Literature Searchmentioning
confidence: 99%